Mixed-Mode Third-Order Quadrature Oscillator Based on Single MCCFTA - K. Khaw-Ngam; M. Kumngern; F. Khateb (My University, 2017)
This paper presents a new mixed-mode thirdorder quadrature oscillator based on new modified current-controlled current follower transconductance amplifier (MCCFTA).The proposed circuit employs one MCCFTA as active element and three grounded capacitors as passive components which is highly suitable for integrated circuit implementation.The condition and frequency of oscillations can be controlled orthogonally and electronically by adjusting the bias currents of the active device.The circuit provides four quadrature current outputs and two quadrature voltage outputs into one single topology, which can be classified as mixed-mode oscillator.In addition, four quadrature current output terminals possess high-impedance level which can be directly connected to the next stage without additional buffer circuits.The performance of the proposed structure has been verified through PSPICE simulators using 0.25 µm CMOS process from TSMC and experimental results are also investigated.
Keywords: Quadrature (astronomy); Third order; Analog and Mixed-Signal Circuit Design